PENJAMIN POLIS ASURANSI OLEH LEMBAGA PENJAMIN SIMPANAN (LPS) - Pohan, Husein; Hendra Sitorus, Deni (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The Deposit Insurance Corporation (DIC) in Indonesia has expanded its role to guarantee insurance policies under Law Number 4 of 2023. This study examines the DIC’s new responsibilities, including regulator, reinsurer, liquidator, risk mitigator, and creditor, and their legal implications. The research highlights potential legal gaps and uncertainties arising from this expanded role, offering valuable insights for policymakers and practitioners. The method used in this research is normative juridical using a statutory regulation approach. The results of this research show that DIC as an insurance policy guarantor has several positions, namely as regulator, Reinsurer, Liquidator, GMS, and Creditor.